Efficacy of Natural Extract from Ocimum Species against Fungus Gnats Infesting Plant Saplings - Kumar, Anya; Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Background: Fungus gnats around household plants besides being annoying can also compromise the growth the plant saplings. Hence effectively repelling them without compromising their ecological purpose is necessary. Materials and Methods: We tested here the effectiveness of an aromatic natural extract of the Ocimum species in repelling the Fungus gnats naturally infesting Catharanthus roseus plant saplings. Ocimum extract was sprayed on the plant saplings and monitored for the presence of the Fungus gnats. The binding potential of selected compounds in the Ocimum extract was evaluated against known insect specific olfactory receptors to understand the mechanism of action. Results: Ocimum extract effectively repelled and reduced the fungus gnats around the plant saplings following treatment over 4 days. This improved the growth of the plant saplings. Selected compounds from Ocimum extract had physiologically effective binding affinity with the insect specific olfactory receptors. Conclusion: Ocimum extract spray is a cost effective and ecologically favourable approach for controlling fungus gnats infesting plant saplings.
Keywords: Fungus gnats; Ocimum extract; Ecological; Cost effective; Insect control; Fly larva; Fly repellent; Plant saplings